The effectiveness of the (Modified SCMP) model in mathematical originality and the attitude of sixth grade students towards mathematical proof (Journal of the College of Basic Education, 2022)
The current research aims to identify the effectiveness of Modified Skemp Model in mathematical originality and attitude of the scientific sixth grade students towards mathematical proof, experimental design of a post-test and partial adjustment of two unequal groups (experimental and control group) was used , the sample of research consist of (55) students from scientific sixth grade students from Ibn Al-Haitham High `School for Boys located in Qadisiyah province, the students were distributed randomly into two groups, one experimental consisting of (28) students studying by (Modified Skemp Model) and the other as control group consisting of (27) students studying by the usual way.Both of groups equivalences in the variables: (chronological age, intelligence, the previous information in math and achievement in math in the last year) experience Applied in the first semester of the academic year (2015 - 2016) one of the researchers studied two groups of research, researchers applied the tools of research (math’s originality test consist of (12) subjective items, and the other tool was ( measurement of attitude toward mathimatical proof which consisted of (33) items.Researchers used a number of appropriate statistical methods to the research objectives, whether for its procedures or the analysis of its results.The search results showed There are existing differences between the two groups experimental and control in the variables of math’s originality and attitude towards mathematical proof in behalf the experimental group In light of the findings of research the researchers reached to several conclusions, recommendations and proposals.